THE MACROECONOMIC POLICY TRAP: LITHUANIAN CASE - Gylys, Povilas (Ekonomika, 2009)
Macroeconomic policy is a major factor of country’s wellbeing. It could be a catalist of the economic growth and could have detrimental impact on the economy. In other words, it may be both public good and public evil. The gist of the given article is to show how cognitive, fiscal and monetary factors influenced Lithuanian economy in both pre-crisis and crisis periods. p>